Serum irisin is positively associated with adiposity markers in obese women after single-session exercise-induced - Bayu Agung Pramono Pramono; Adi Pranoto; I Dewa Made Aryananda Wijaya Kusuma; Ghana Firsta Yosika; Yanyong Phanpheng (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The link between serum irisin levels and body fat markers has long been questioned in adult populations. However, there is scant research specifically addressing this link in obese female individuals. This study will thoroughly evaluate the relationship between serum irisin levels and adiposity indices in an obese female population. The study involved a group of 40 women, aged between 20 and 24 years, who were experiencing obesity. The correlations of serum irisin with adiposity markers measurements were determined. The statistical evaluation was conducted using a parametric linear correlation approach. Serum irisin levels, quantified in ng/mL, positively correlated with several adiposity indicators. Notably, there was a meaningful relationship with body weight in kilograms (r = 0.385, p = 0.014), body mass index (BMI) (r = 0.588, p ≤ 0.001), body fat percentage (r = 0.450, p = 0.004), total fat mass in kilograms (r = 0.342, p = 0.031), and lean body mass in kilograms (r = 0.344, p = 0.029). Furthermore, waist circumference in centimeters (r = 0.329, p = 0.038), hip circumference in centimeters (r = 0.321, p = 0.043), and the waist-to-hip ratio (r = 0.447, p = 0.004) also demonstrated positive correlations with irisin concentrations. Conversely, body height in meters showed no significant correlation (r = -0.003, p ≥ 0.05). Serum irisin’s relationship with adiposity markers is evident, yet it does not extend to body height. Interrelationships among adiposity markers might influence serum irisin in obese women after single-session exercise.